SU(3)CIRCLE-TIMES-U(1) MODEL FOR ELECTROWEAK INTERACTIONS - Pisano, F.; Pleitez, Vicente [UNESP] (American Physical Soc, 1992)
We consider a gauge model based on a SU(3)XU(1) symmetry in which the lepton number is violated explicitly by charged scalar and gauge bosons, including a vector field with double electric